1977
DOI: 10.7901/2169-3358-1977-1-529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chesapeake Bay Oil Spill on Salt Marshes of the Lower Bay

Abstract: A study to determine the effects of the Chesapeake Bay oil spill of February 1976, and of the subsequent cleanup operations was conducted on the eastern shore of the Bay. The primary objective was to assess the biological impact on the marshes at the population level. Populations of intertidal mussels, Modiolus demissus, and oysters, Crassostrea virginica, showed no significant short-term effects. The population of the snail, Littorina irrorata, was significantly reduced, but appears to be recovering well. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Nyman [76] found that Louisiana and Arabian crude oils accelerated, rather than slowed, microbial activity in fresh marsh soils. Accelerated organic matter mineralization suggests increased nutrient re-mineralization rates and may help explain the reported observations of enhanced plant growth following exposure of S. alterniflora [20,48,77]) and S. lancifolia [21] to oil. However, additional data on the effects of other oils and the responses of marsh plants is needed before definitive cause and effect relationships can be established [2].…”
Section: Oil Coverage Of Plant Leaves Versus Coverage and Penetrationmentioning
confidence: 79%
“…Nyman [76] found that Louisiana and Arabian crude oils accelerated, rather than slowed, microbial activity in fresh marsh soils. Accelerated organic matter mineralization suggests increased nutrient re-mineralization rates and may help explain the reported observations of enhanced plant growth following exposure of S. alterniflora [20,48,77]) and S. lancifolia [21] to oil. However, additional data on the effects of other oils and the responses of marsh plants is needed before definitive cause and effect relationships can be established [2].…”
Section: Oil Coverage Of Plant Leaves Versus Coverage and Penetrationmentioning
confidence: 79%
“…Height and density measurements for smooth cordgrass in other regions and seasons are abundsnt (Nixon and Oviatt~ 1973;Williams and Mur~och~ 1969;Turner and Gosselink, 1975;Hershner and Moore, 1977;Reimold and Linthurst , 1977 ; and many others).…”
Section: P!ant Data Analysismentioning
confidence: 99%
“…A few studies have documented impacts on marsh periwinkles following prior oil spills, with effects including increased mortality, reduced density, reduced recruitment, and altered snail size distributions (Hershner & Moore 1977, Hershner & Lake 1980, Krebs & Tanner 1981, Lee et al 1981. However, each of these spills differed from the Deepwater Horizon incident in several important ways: (1) all were located outside the Gulf of Mexico region; (2) all were shallow, nearshore spills or experimental oil applications that rapidly affected shorelines, whereas oil from the offshore Deepwater Horizon release weathered at sea for 2 wk or more before reaching shore; (3) all were spills of refined products, including No.…”
Section: Introductionmentioning
confidence: 99%